Association of high IFN-γ plasma levels with low B-cell counts in renal transplant recipients with stable long-term graft function - Daniel, Volker; Naujokat, Cord; Sadeghi, Mahmoud; Renner, Fabrice Christoph; Weimer, Rolf; Opelz, Gerhard (Clinical transplantation, 2010)
Recently, we reported that patients with long-term stable good graft function had higher interferon-gamma (IFN-gamma) and lower IL-4 plasma levels late as compared with early post-transplant. These patients had more often detectable CD3(+)CD4(+)CD25(+)IFN-gamma(+)Foxp3(+) peripheral blood lymphocytes (PBL) late post-transplant than patients with impaired graft function. We therefore speculated that high plasma IFN-gamma late post-transplant might contribute to the maintenance of graft acceptance. Using ELISA and four-color flow cytometry, plasma cytokines and PBL subpopulations were measured in 65 renal transplant recipients with stable graft function late post-transplant. High IFN-gamma plasma levels were associated with low CD19(+) B PBL (r = -0.329; p = 0.009) and low activated CD3(+)CD8(+)DR(+) T PBL (r = -0.266; p = 0.035). Plasma IFN-gamma increased with time post-transplant (r = 0.288; p = 0.022) and was not associated with the dose of immunosuppressive drugs (p = n.s.). High plasma IFN-gamma was not associated with serum creatinine (r = 0.038; p = 0.765). Five patients showed evidence of chronic allograft nephropathy in previous biopsies and none of them exhibited increased plasma IFN-gamma. In patients with good long-term graft function, high IFN-gamma plasma levels were associated with low numbers of B PBL and activated CD8(+) T PBL. High IFN-gamma plasma levels might prevent the development of an immunological alloresponse and thereby contribute to the maintenance of graft acceptance.
Gesehen am 07.08.2023